Jornada médica: panorama social e cultural - Dutra, Jhonatan Vinicius de Sousa (Universidade Federal de São Carlos, 2025)
Medical education is a complex and multifactorial process, marked by personal, social, and academic challenges. This work presents a reflection on the trajectory of a low-income medical student, highlighting the difficulties faced and overcome through family support, academic dedication, and involvement in extracurricular activities. The active learning methodology, a distinctive feature of the institution, proved fundamental in developing clinical reasoning, ethical-professional preparation, and medical identity. Scientific evidence on mental health, educational methodologies, and socioeconomic impacts were integrated, emphasizing the relevance of resilience, social support, and innovative pedagogical practices in shaping future physicians. The study demonstrates that the construction of professional identity goes beyond the accumulation of technical knowledge, encompassing ethical, emotional, and social dimensions.
Medical journey: social e culture overview
Keywords: Educação médica; Metodologias ativas; Saúde mental; Formação médica; Identidade profissional; Medical education; Active learning; Mental health; Medical training; Professional identity; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 3. Saúde e Bem-Estar; 4. Educação de Qualidade